Kualitas Informasi, Keterlibatan Kerja, dan Gaya Kepemimpinan sebagai Faktor Penentu Efektivitas Pengambilan Keputusan Organisasional - Mardikaningsih, Rahayu; Sifa, Nur Vianti Lailatus (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This quantitative study examines the influence of information quality, work engagement, and leadership style on decision making effectiveness among employees of a manufacturing company. Data were collected from 100 respondents using accidental sampling technique. Multiple linear regression analysis revealed that all three independent variables simultaneously affect decision making effectiveness. Partially, information quality, work engagement, and leadership style each have significant positive effects on decision making effectiveness. Leadership style demonstrates the strongest influence, followed by information quality and work engagement. The regression equation indicates positive contributions from all predictors. The coefficient of determination shows that the three predictors collectively explain a substantial portion of variance in decision making effectiveness. Findings suggest manufacturing companies should prioritize transformational leadership development programs, conduct information system audits, and implement work engagement initiatives to enhance decision making effectiveness. Future research should expand to other industries, add organizational culture variables, and employ longitudinal designs.